Effectiveness Of Sidaguri Extract (Sida Rhombifolia) On Postpartum Perineum Wound Healing - Kasmiati Kasmiati; Dia Rianti; Fardiansyah Fardiansyah (International Journal of Health and Pharmaceutical (IJHP), 2023)
Perineal trauma which is a common complication that occurs after childbirth is in 55%-85% of vaginal births. Infection in the postpartum period if not treated properly will be a complication of 1% - 4%. So it is very important in providing care for perineal tears in postpartum mothers, the purpose of this study was to see the Effectiveness of Sidaguri Extract (Sida Rhombifolia) Against Perineal Wound Healing in Postpartum. The research method used a True Experimental design with a Control Group. This research was carried out at the UPTD Puskesmas Watampone Kab. Bone. The sample of this study was postpartum mothers who came to visit and received postpartum services from June 29 - August 29, sampling using an accidental sampling technique obtained 24 samples, and data analysis using the MannWhitney U test. The results of the application of Sida Rhombifolia extract on postpartum maternal perineal wounds showed a significant p-value (0.00) which means that Sida Rhombifolia extract was able to accelerate the healing of perineal tears. So Sida Rhombifolia extract can be an alternative in providing care, prevention, and accelerating the healing of perineal tears in postpartum mothers.